New records of bathyal Leptolida (Cnidaria: Hydrozoa: Leptothecata) from the Bay of Biscay and the northwestern Iberian Peninsula (northeastern Atlantic) - Altuna, Álvaro (Zootaxa, 2012)
Four uncommon bathyal thecate hydroids, Plicatotheca anitae Calder & Vervoort, 1986, Zygophylax africana Stechow,1923, Nemertesia falcicula (Ramil & Vervoort, 1992a) and Pseudoplumaria marocana (Billard, 1930), were collectedduring benthic surveys of the Cantabrian Sea and the Galicia Bank (Spain, northeastern Atlantic). Northern ranges of allfour are extended in the Atlantic Ocean. Elsewhere in the northeastern Atlantic, Plicatotheca anitae is known only fromthe Azores, while the nearest records of Nemertesia falcicula and Pseudoplumaria marocana are the Strait of Gibraltarand from a station northwest off Cape San Vicente in the south of Portugal, respectively. Zygophylax africana, known onlyfrom South Africa and Japan, is new to the European fauna and was obtained at an unusual depth. Each of the four species is described and illustrated, and their distributions and bathymetric ranges are revised.